2004
DOI: 10.1161/01.atv.0000139010.71779.f3
|View full text |Cite
|
Sign up to set email alerts
|

B-Myb Represses Vascular Smooth Muscle Cell Collagen Gene Expression and Inhibits Neointima Formation After Arterial Injury

Abstract: Objectives-The function of B-Myb, a negative regulator of vascular smooth muscle cell (SMC) matrix gene transcription, was analyzed in the vasculature. Methods and Results-Mice were generated in which the human B-myb gene was driven by the basal cytomegalovirus promoter, and 3 founders were identified. Mice appeared to develop normally, and human B-myb was expressed in the aortas. Total B-Myb levels were elevated in aortas of adult transgenic versus wild-type (WT) animals and varied inversely with ␣1(I) collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Hence, mutants of Dm-Myb have various mitotic defects, including centrosome amplification and genome instability (Fung et al, 2002), which may in part be due to a requirement for Dm-Myb to induce cyclin B expression (Okada et al, 2002). In addition, studies in neuroblastoma and B-cell lines have implicated B-Myb as a differentiation and antiapoptotic factor (Raschella et al, 1995;Lang et al, 2005), while B-Myb has been shown to regulate extracellular matrix molecule gene expression in vascular cells (Hofmann et al, 2004) and adhesion molecule expression in embryonic stem (ES) cells (Iwai et al, 2001).…”
mentioning
confidence: 99%
“…Hence, mutants of Dm-Myb have various mitotic defects, including centrosome amplification and genome instability (Fung et al, 2002), which may in part be due to a requirement for Dm-Myb to induce cyclin B expression (Okada et al, 2002). In addition, studies in neuroblastoma and B-cell lines have implicated B-Myb as a differentiation and antiapoptotic factor (Raschella et al, 1995;Lang et al, 2005), while B-Myb has been shown to regulate extracellular matrix molecule gene expression in vascular cells (Hofmann et al, 2004) and adhesion molecule expression in embryonic stem (ES) cells (Iwai et al, 2001).…”
mentioning
confidence: 99%
“…However, our data clearly demonstrate that the genetic background of mice has a considerable influence on the extent of neointima formation in response to vascular injury. Although much effort has been spent on optimizing technical aspects of injury models and on studying mitogenic or endothelial factors (3,8,11,16), it may even be hypothesized that an optimal genetic background of mice may be necessary to unravel a significant influence of a certain factor. In our studies, we used mice of a mixed background that were backcrossed into either the 129 strain or the DBA strain.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental approaches aimed at understanding the molecular details of neointimal formation by analysis of gene expression could contribute to the development of treatments with reduced side effects. [11][12][13][14][15] So far, the best characterized animal model for study of the arterial duct is the sheep. The genomic sequence of the sheep, however, is not yet completed.…”
Section: T He Arterial Duct Provides the Necessarymentioning
confidence: 99%